EDUCATION INNOVATION AND DIGITALISATION AS THE KEY TO GLOBAL COMPETITIVENESS - Loso Judijanto; Siti Indah; Naf’an Torihoran (Indonesian Journal of Education (INJOE), 2024)
In the era of globalisation and industrial revolution 4.0, innovation and digitalisation of education have become crucial factors in improving the global competitiveness of a nation. The research method used in this study is literature. The results show that effective integration of technology in the education system can create a learning environment that is more adaptive, personalised and relevant to the needs of the global market. Therefore, the importance of a holistic approach that considers aspects of accessibility, data security, and inclusion in the process of digitalisation of education